Effects of black cohosh and estrogen on core body and tail-skin temperatures in ovariectomized rats by telemetric monitoring with dual thermistor probes. (4th March 2018) - Sun, Y.; Qin, L. H.; Chen, X.; Yan, X.; Mao, L.; Bai, W.; Kang, J.
Abstract: Objectives: To investigate the effects of black cohosh and estrogen on the temperature in ovariectomized rats, the core body temperature (CBT) and tail-skin temperature (TST) were simultaneously monitored and the relationship between these two temperatures was explored. Methods: Twenty-four female Sprague–Dawley rats aged 8 weeks were randomly divided into four groups: sham-operated (SHAM), ovariectomized (OVX), OVX treated with estradiol valerate (OVX + E), and OVX treated with isopropanolic black cohosh extract (OVX + ICR). Rats were sham-operated or ovariectomized and were implanted with telemetry transmitters with dual thermistor probes. Two weeks after surgery, the animals were treated with drugs for 4 weeks. During the last week of the treatments, the dynamic temperature profiles of the CBT and TST were collected. Results: The average CBT and TST, TST fluctuation frequency, and the average amplitude fluctuation were significantly higher in OVX than in SHAM rats. In addition, dramatic fluctuations of TST in OVX rats occurred at the time points of the day when the CBTs were lower in OVX rats than in SHAM rats. Treatment of OVX rats with estradiol valerate or isopropanolic black cohosh extract markedly decreased the average CBT and TST, TST fluctuation frequency, and the average amplitude fluctuation. Moreover, CBT was found to be significantly higher, while TST was lower in OVX + E than in OVX + ICR rats. Conclusions: Both black cohosh and estradiol treatments ameliorated the abnormal thermoregulation in OVX rats. In particular, black cohosh reduced CBT better than estradiol and estradiol reduced TST better than black cohosh.